Descriptive ecology of abyssal decapods from Chapopote Knoll (southwestern Gulf of Mexico) - Adriana Gaytán-Caballero; Florence Schubotz; Ian R. MacDonald; Elva G. Escobar-Briones (Frontiers in Marine Science)
The Chapopote Knoll at 3200 m depth, in the southern Gulf of Mexico harbors highly diverse benthic habitats, including massive asphalt flows and surficial gas hydrates with gas seepage. Its associated benthic megafauna includes endemic cold-seep species and background species. This study describes the benthic habitat preferences, distribution patterns and diets of three crustacean species, the caridean shrimp Alvinocaris muricola and the galatheids Munidopsis geyeri and M. exuta. High-resolution imaging recorded eight habitats and helped depict their spatial distributions. A. muricola aggregates on Siboglinidae clusters and in gas seepage sites. M. geyeri and M. exuta are less selective and occur in almost all habitats. The carbon (δ13C) and nitrogen (δ15N) values of A. muricola show a nutritional preference of bacteria from mats and water column detritus retained among the Sibolindiae, whereas the two Munidopsis species have wider spectrum diets. Gut content analysis in all three species, validate the stable isotope values, food sources and confirm the secondary consumer’s trophic level. This study recognizes coexistence of A. muricola and the two Munidopsis species in the benthic habitats while using different resources. Compound specific isotope analyses of galatheid guts revealed females to have more 13C-depleted lipids (-35‰) compared to males (-28‰), calling for more detailed analyses to clarify this trophic segregation.